Green Synthesis Nanoparticle ZnO Sargassum sp. Extract and The Products Charactheristic - Rodiah Nurbaya Sari; N. Nurhasni; M. Ainul Yaqin (Department of Aquatic Product Technology IPB University in collaboration with Masyarakat Pengolahan Hasil Perikanan Indonesia (MPHPI), 2017)
The synthesis of zinc oxide (ZnO) nanoparticles is an emerging research area due to its wide range of applications, such as electronics, pharmaceuticals, optics and food packaging. In this study, described the green synthesis of ZnO nanoparticles and their characteristics using Sargassum sp. extract and 0.1 M zinc nitrate as the precursors. The variations include Sargassum sp. extracts volume of 5, 10, and 20mL and the calcination temperature of 400, 500, and 600 oC. The characterization had been done such as the role of Sargassum sp. extract as a reducing agent for Zn2+ → Zn0 confirmed by Fourier Transform Infrared Spectroscopy (FTIR) spectra due to 450-4000 cm-1 wavelength, the size of particles using Particle Size Analyzer (PSA), image and chemical composition using Scanning Electron Microscopy with X-ray microanalysis (SEM-EDS) and crystallinity using ray powder diffraction (XRD) with Cu anode at 1.54187 Å. Analysis with PSA instrument showed that ZnO particle size increased from 607 up to 649 nm along with increasing of extract concentration from 5 up to 20% (v/v). SEM imaging showed the formation of ZnO to be predominantly spherical and EDS data confirmed the existence of zinc and oxygen in the particles obtained. XRD analysis revealed hexagonal crystal system of ZnO nanoparticles and decreased in crystallite size was observed from 31.4 to 14.7 nm with increased in calcination temperature from 400 to 600 oC.